2016
DOI: 10.1074/jbc.m116.733972
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone (FSH)-dependent Regulation of Extracellular Regulated Kinase (ERK) Phosphorylation by the Mitogen-activated Protein (MAP) Kinase Phosphatase MKP3

Abstract: Within the ovarian follicle, granulosa cells (GCs) surround and support immature oocytes. FSH promotes the differentiation and proliferation of GCs and is essential for fertility. We recently reported that ERK activation is necessary for FSH to induce key genes that define the preovulatory GC. This research focused on the phosphoregulation by FSH of ERK within GCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 82 publications
4
24
0
Order By: Relevance
“…The proteasome inhibitor MG-132 prevents DUSP6 degradation, indicating the ubiquitin-proteasomal pathway is involved in this process. The degradation of DUSP6 protein is inversely correlated with the phosphorylation of ERK1/2 and indeed, as the DUSP6 inhibitor BCI enhances ERK1/2 phosphorylation, this protein phosphatase appears to be involved in regulating basal cytosolic ERK activation (Donaubauer et al, 2016 ). The specificity of BCI as an inhibitor of DUSP6 was first reported by studying the FGF-mediated increase in ERK signaling in zebrafish embryos (Molina et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteasome inhibitor MG-132 prevents DUSP6 degradation, indicating the ubiquitin-proteasomal pathway is involved in this process. The degradation of DUSP6 protein is inversely correlated with the phosphorylation of ERK1/2 and indeed, as the DUSP6 inhibitor BCI enhances ERK1/2 phosphorylation, this protein phosphatase appears to be involved in regulating basal cytosolic ERK activation (Donaubauer et al, 2016 ). The specificity of BCI as an inhibitor of DUSP6 was first reported by studying the FGF-mediated increase in ERK signaling in zebrafish embryos (Molina et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…While DUSP6 expression is enhanced in some kinds of cancer (melanoma and glioma cells), suggesting it may be a tumor promotor (Messina et al, 2011 ; Li et al, 2012 ), its expression is dampened in other tumors where it may exert a role as a tumor suppressor, such as pancreatic invasive cancer, primary lung cancer and ovarian cancer (Furukawa et al, 2003 ; Chan et al, 2008 ; Okudela et al, 2009 ). Significantly, very little is known about the intrinsic regulation of DUSP6 in native tissues and its modulation by endogenous extracellular signals that activate receptor tyrosine kinases (RTKs) e.g., mitogens (Ham et al, 2015 ; Donaubauer et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblot, Immunoprecipitation, and Cell-free PKA Phosphorylation Assay-Following treatments, cells were collected and processed according to procedures described previously (31,77).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, luteinizing hormone (LH) and follicle stimulating hormone (FSH) are the primary drivers of ovarian follicle growth and stimulators of the granulosa cells surrounding the developing oocyte [ 54 ]. A study performed on rat granulosa cells demonstrated that Dusp6 in the granulosa cells keeps ERK inactivated in the absence of FSH [ 55 ]. Once maturation is initiated by FSH, PKA is activated through cAMP to inhibit Dusp6, thereby allowing active pERK to accumulate and drive downstream genes promoting oocyte maturation and progression through the meiotic cell cycle [ 56 ].…”
Section: Discussionmentioning
confidence: 99%